Spectres of 1919 : Class and Nation in the Making of the New Negro - Foley, Barbara, 1948- (Book collections on Project MUSE., 2008)
A look at the violent "Red Summer of 1919" and its intersection with the highly politicized New Negro movement and the Harlem Renaissance.